The Counter-Narratives of Radical Theology and Popular Music
VII, 222 p. 1 illus.
Keywords: In this unique collection, theologians born and formed during the Cold War offer their insights and perspectives on theological relationships with such musical artists and groups as Joy Division, U2, Nick Cave, and John Coltrane. These essays demonstrate that one's personal music preferences can inform and influence professional interests.